2005
DOI: 10.1016/j.gene.2005.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The properties of CpG islands in the putative promoter regions of human immunoglobulin (Ig) genes

Abstract: CpG is a GC rich motifs in the gene promoter region, which can play important roles in gene silencing and imprinting. This study examines the properties of CpG islands in the putative promoter regions have the CpG distributions in the two patterns. Moreover, the length of CpG islands is shorter in human Ig genes than in non-Ig genes, but much longer than in mouse orthologous. Thus, our data suggest that the occurrence and distribution of CpG islands in PPRs of human and mouse Ig genes is nonneutral and nonrand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Recent studies identi ed the novel role of REC8 as a potential tumor-suppressor gene. REC8is hypermethylated in many cancers, including melanoma, thyroid cancer, and malignant gastrointestinal stromal tumor [36][37][38].Epigenetic inactivation of REC8 predicts worse survival outcomes in patients with thyroid and gastric cancers. Moreover, Liu et al reported that REC8 is aberrantly methylated and robustly regulated by the phosphoinositide-3 kinase pathway in thyroid cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies identi ed the novel role of REC8 as a potential tumor-suppressor gene. REC8is hypermethylated in many cancers, including melanoma, thyroid cancer, and malignant gastrointestinal stromal tumor [36][37][38].Epigenetic inactivation of REC8 predicts worse survival outcomes in patients with thyroid and gastric cancers. Moreover, Liu et al reported that REC8 is aberrantly methylated and robustly regulated by the phosphoinositide-3 kinase pathway in thyroid cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…50 (Gardiner-Garden and Frommer 1987). The method used for CpG island identification was according to a previous report (Takai and Jones 2002;Liu et al 2005) with some modifications. Briefly, a SW of 200 bp was applied from the 5 0 end of the DNA sequence, and the G% þ C% and O/E value of the CpGs within the SW was computed.…”
Section: Cpg Island Identificationmentioning
confidence: 99%
“…As shown in the Table II, 120 genes (17.6%) out of 682 genes contained TATA box, and 191 (28.0%) contained GC box and 129 (18.9%) contained CAAT box in their PPRs (Table II). We also calculated the actual number and frequency of the genes that contain CpG islands in their PPRs by using our reported method (Liu et al 2005). As a result, 262 genes (38.4%) contained CpG islands (Table II).…”
Section: Base Composition Pattern In Relation To the Core Promoter Elmentioning
confidence: 99%